PENGARUH PENGENCERAN DAN PENGADUKAN LIMBAH INDUSTRI IKAN NILA TERHADAP PENINGKATAN PRODUKSI BIOGAS DENGAN MENGGUNAKAN RUMEN SAPI SEBAGAI STARTER - Muhammad Fachri Maulana; Sudarno Sudarno; Irawan Wisnu Wardhana (Departemen Teknik Lingkungan Fakultas Teknik Universitas Diponegoro, 2013)
Tilapia fish industry solid waste is resulting from the process of weeding, washing, and preparation. Tilapia fish industry solid waste has a high content of organic material. This would give to environmental issues when waste disposed into the environment. Therefore, an alternative processing by converting solid waste into biogas from Tilapia fish industry solid waste with anaerobic process. This research aims to enhancement of biogas production from Tilapia fish industry solid waste by using a rumen as a starter. The treatment was by dilution and stirring intencity in a samples with crushed and without crushed. This research is an experimental-laboratoris, where research is done in a scale laboratory. Methods used to research is a batch reactor using in anaërobic fermentation process. The results of this research show that Fish tilapia industry solid waste can generate biogas after rumen fluid with anaerobic processes continuously until 20 days. On the variable of the total volume production results in dilution of wastewater occur at the highest addition of water 150 ml with the treatment without chrushed i.e. 816 ml. On the variable total production volume result of stirring biogas high occur in stirring 3 x 150 ml with the dilution of the treatment without chrushed i.e. 1057 ml. On these variables was determine the influence measurement of chemical oxygen demand (COD) allowance against the production of biogas produced. The efficiency removal of COD occur at the highest stage without stirring sample A 100 ml a dilution that is 91%. The whole pH measurements on a variable decrease from the initial pH values 7 to pH 5.